Clinical research Antiviral activity of borage (Echium amoenum) - Abolhassani, Mohsen (Archives of Medical Science, 2010)
Introduction: Borage (Echium amoenum) is a large annual plant of the Boraginaceae family that grows in most parts of Europe and in northern parts of Iran. The flower of borage is used as a medicinal herb in various countries as an antifebrile and antidepressant, for treatment of stress, circulatory heart diseases and pulmonary complaints, as a poultice for inflammatory swellings, as a diuretic, laxative, emollient and demulcent, and recently as a possible cancer protective factor. The Iranian borage is used in traditional medicine for infectious diseases and influenza and as an antifebrile. In this report, an aqueous extract of dried borage (Echium amoenum) flowers was tested in vitro for its antiviral activity. Material and methods: Bacteriophage 3C and its specific host, Staphylococcus aureus 8327 were used Aqueous extract of E. amoenum dried flower was prepared and anti-viral activity was determined by agar overlay method and the burst size was determined by one-step growth experiment. Antibacterial activity was determined by disc diffusion, agar-well diffusion and minimum inhibitory concentration methods. Results: The extract showed concentration-dependent antiviral activity against free bacteriophage 3C and reduced the yield of phage from the host Staphylococcus aureus 8327. Antiviral activity of the extract is heat resistant. Autoclaving the extract at 110°C for 1 h did not eliminate its antiviral activity and the effect was similar to the extract that was filter sterilized. However, the activity of the freeze-dried extract was diminished during 90 days of storage at 4°C and the activity of the working solution was diminished in a one-week period at 4°C. Conclusions: These results may provide a justification for the traditional use of the Iranian borage flower for infectious diseases and antifebrile activity.